Extending integrated assessment models′ damage functions to include adaptation and dynamic sensitivity. (November 2019) - Estrada, Francisco; Tol, Richard S.J.; Botzen, W.J. Wouter
Abstract: Through stylized damage functions, Integrated Assessment Models (IAMs) provide estimates of the economic costs that would occur for absolute changes in global temperature. In these damage functions, adaptation, sensitivity and their interactions are often combined in an intractable way. In this theoretical study we propose a new type of damage functions that allows mapping economic losses in terms of how extreme global temperature changes are in relation to a coping range representing the capacity of a system to deal with the climate conditions experienced at a particular period of time. In these new damage functions, which can be applied to the regional and global scales, adaptation to a changing climate is introduced by allowing the reference climate to be a function of time instead of a fixed quantity. Different formulations of damage functions discussed in the literature arise as special cases. Highlights: Economic IAMs commonly use stylized damage functions with implicit adaptation and fixed sensitivity. Such specification precludes any dynamic representation of the systems affected by climate change. IAMs projections of the costs of climate change are highly sensitive to these assumptions. Here we present a new type of damage function that allows for interactions between impacts, sensitivity and adaptation. These new damage functions allow for path and time dependence of impacts, adaptation capacity/response and sensitivity. Particular formulations of damage functions discussed in the literature arise as special cases